Altered function of CCK-positive interneurons in mice over-expressing the schizophrenia risk gene neuregulin 1 - Kotzadimitriou, D (2016)
The Neuregulin 1 (NRG1)-ErbB4 signalling pathway is implicated in critical processes for the development and function of neuronal circuits. Post mortem studies have reported that elevated expression of NRG1 type 1 isoform is associated with schizophrenia. Importantly previous behavioural studies in mice that overexpress the NRG1 type 1 isoform (NRG1tg-type-I) have suggested a schizophrenia endophenotype including impairment in the hippocampus-dependent spatial working memory, prepulse inhibition (PPI) of the startle reflex and alterations in the gamma band rhythmogenesis This study aims to reveal the cellular targets of the NRG1-ErbB4 signalling pathway and putative alterations in the function of the hippocampal network in NRG1tg-type-I mice. Immunocytochemical analysis showed that the NRG1 receptor ErbB4 is predominantly localized in interneurons comprising parvalbumin positive (PV) and cholecystokinin (CCK) expressing cells. Comparison of the density of ErbB4-positive cells between the hippocampus of wild type (WT) and NRG1tg-type-I mice suggested that NRG1 over-expression resulted in decreased number of ErbB4 immunopositive hippocampal interneurons. This is consistent with the proposed role of the NRG1-ErbB4 signalling in the migration of GABAergic cells during neurodevelopment and with the NRG1-mediated internalisation of the ErbB4 receptors. CCK- positive cells are a major target of NRG1-ErbB4 signalling, and therefore the NMDA receptor and AMPA receptor components of glutamatergic transmission were analysed in this population of cells by performing whole cell recordings of evoked and miniature excitatory post synaptic currents. Glutamatergic neurotransmission in CCK-positive cells was found to be compromised in the hippocampus of NRG1tg-type-I mice. This change was attributed to hypofunction of NMDA receptors but not AMPA receptors post-synaptically. Next, the inhibitory output of CCK-positive cells to pyramidal cells was examined. Analysis of the optogenetically elicited inhibitory post synaptic currents (IPSCs) did not reveal any changes in the properties of the GABAergic synapse formed by these cells due to NRG1 over-expression Finally, the effects of this NMDA receptor hypofunction in the recurrent inhibition were analysed by performing whole cell recordings during the gamma relevant optogenetic entrainment of the hippocampal network. It was found that the disynaptic inhibition, a key synaptic interaction for the generation of gamma oscillations, depends on the NMDA receptors and was altered in the hippocampus of NRG1tg-type-I mice. Together these data point out a key modulatory role of the NRG1-ErbB4 signalling in the neurodevelopment of cortical microcircuits and a link between ErbB4 and NMDA receptor function with a possible association to schizophrenia pathogenesis.